2017
DOI: 10.33549/physiolres.933627
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neurogenesis in the Hippocampus From a Perspective of Discrimination and Generalization: A Hypothesis

Abstract: The function of adult neurogenesis in the dentate gyrus is not yet completely understood, though many competing theories have attempted to explain the function of these newly-generated neurons. Most theories give adult neurogenesis a role in aiding known hippocampal/dentate gyrus functions. Other theories offer a novel role for these new cells based on their unique physiological qualities, such as their low excitability threshold. Many behavioral tests have been used to test these theories, but results have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Microglia also contributes substantially to adult neurogenesis [ 10 , 120 123 ], which takes place in the dentate gyrus for the hippocampus [ 124 ], the subventricular zone for the olfactory system [ 125 , 126 ] and in the hypothalamus for the neuro-endocrine system [ 127 ]. Life-long adult neurogenesis is required for the function of memory, olfaction, neuroendocrine system and possibly others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia also contributes substantially to adult neurogenesis [ 10 , 120 123 ], which takes place in the dentate gyrus for the hippocampus [ 124 ], the subventricular zone for the olfactory system [ 125 , 126 ] and in the hypothalamus for the neuro-endocrine system [ 127 ]. Life-long adult neurogenesis is required for the function of memory, olfaction, neuroendocrine system and possibly others.…”
Section: Introductionmentioning
confidence: 99%
“…Life-long adult neurogenesis is required for the function of memory, olfaction, neuroendocrine system and possibly others. As for the development of the CNS, in adult neurogenesis, enhanced or reduced generation of new neurons and their integration may substantially influence the brain function [ 124 ]. Neurogenesis is influenced by microglia [ 128 ] either by producing corresponding supporting or suppressing factors, or by eliminating new neurons [ 129 ], as well as by sustaining new neurons alive.…”
Section: Introductionmentioning
confidence: 99%
“…Adult hippocampal neurogenesis provides the structural plasticity to hippocampal networks to enhance the adaptability of animal to environmental stress [ 3 ]. In the dentate gyrus (DG) region of the hippocampus, neural stem cells (NSCs) experience the systematic biological events from proliferation, neural fate commitment, neural differentiation and maturation that form the newborn neurons to integrate into neural circuits [ 4 ]. The new formed neurons in DG region engage the hippocampus to separate the environmental cues and support the discrimination among the danger and safety surroundings [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin is a kind of lipid-lowering drug. In recent years, studies have found that simvastatin can also promote nerve regeneration and protect neurological function [3] . Hippocampus is closely related to learning and memory function and is often involved in cerebral ischemia [4] .…”
mentioning
confidence: 99%